Pharmacy Students’ Clinical Reasoning and Decision-Making to Detect and Resolve Medication Errors - Maguy Saffouh El Hajj (14151477) (2025)
Objective Medication errors pose a significant challenge in health care, impacting patient safety. Pharmacists play a key role in mitigating errors by using clinical reasoning skills. This study examined Qatar University College of Pharmacy students’ clinical reasoning and decision-making processes in case scenarios involving medication errors. Methods A qualitative case study using the think-aloud procedure was conducted with senior fourth-year Bsc Pharm and PharmD students, using the Clinical Reasoning Model. Data were analyzed thematically. Results A total of 25 interviews were conducted and 8 themes were identified as follows: (1) Gaining Initial Patient Impression, (2) Assessing Patient Data, (3) Difficulty Recalling Therapeutic Knowledge, (4) Interpreting Patient Data, (5) Synthesizing Facts and Inferences for a Definitive Diagnosis of Errors, (6) Describing Desired Outcomes, (7) Optimizing Decision-Making, and (8) Process and Recommendations. Conclusion Qatar University student pharmacists used various strategies to detect and resolve medication errors. The think-aloud procedure offered insights into factors influencing clinical reasoning and decision-making, highlighting the importance of future educational interventions to further develop students’ skills. Other Information Published in: American Journal of Pharmaceutical Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajpe.2025.101449